2000
DOI: 10.1177/136345930000400204
|View full text |Cite
|
Sign up to set email alerts
|

Social Realities of Loss and Suffering Following Mastectomy

Abstract: This article draws on personal accounts of women’s thoughts and feelings following mastectomy. The analysis of the material obtained in multiple, focused interviews has revealed two major themes in these accounts: on the one hand, the loss of bodily symmetry (one of the basic cultural criteria of physical beauty) was deeply felt; and on the other, peace of mind (a characteristic of psychological beauty) was permanently disturbed by the fear of the recurrence of cancer and the possibility of death. While the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
18

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 35 publications
0
53
0
18
Order By: Relevance
“…As such, it can be argued that patients can experience biographical disruption not only at point of diagnosis, but also when they leave the sick role and enter an interim state situated between being ill and being fully restored to a pre-diagnosis state of health. This interim state may be conceptualised as liminality (Powers et al, 2014;Blows et al, 2012;Crouch & McKenzie, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it can be argued that patients can experience biographical disruption not only at point of diagnosis, but also when they leave the sick role and enter an interim state situated between being ill and being fully restored to a pre-diagnosis state of health. This interim state may be conceptualised as liminality (Powers et al, 2014;Blows et al, 2012;Crouch & McKenzie, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, just one study was identified which focussed specifically on breast cancer (Crouch & McKenzie, 2000) but only included 7 participants. Therefore, this study of 24 women who had completed treatment up to 29 years earlier enables a longer term and more in depth consideration of ongoing disruptions to identities, bodies and relationships, from diagnosis of breast cancer to the end of treatment, and well beyond.…”
Section: Introductionmentioning
confidence: 99%
“…Crouch and McKenzie's work (2000), entitled as social realities of loss and suffering following mastectomy, revealed that patients undergone mastectomy suffer from feeling of not having body balance which is a major factor in physical attractiveness, and lack of mental peace as a key indicator in mental attractiveness because of fear frm disease recurrence and death hazard. Both factors result in reduction of quality of life to a great extent (Crouch et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In a review of the existential challenges faced by individuals with cancer, Henoch & Danielson (2009) reported that patients often perceive a range of threats to their self-identity and may struggle to maintain this. Research involving individuals in the post-treatment phase has shown that adverse effects may be felt by those whose sense of identity may still carry a stigma of being a cancer patient (Crouch & McKenzie, 2000). In the present study, the loss of identity had, for some, been specifically linked to gender roles, whereas for others, it had related to a general sense of lacking ability.…”
Section: Meaningmentioning
confidence: 53%
“…Some researchers have, however, examined existential experiences as part of wider research objectives. For example, explorations of the discordant feelings of cancer survivors have shown that many individuals who had been symptom free of cancer for up to two years tend to experience existential concerns relating to isolation and death (Crouch & McKenzie, 2000). Similarly, an examination of the supportive care needs of women following treatment for a gynaecological cancer by Hodgkinson et al (2007) found that the participants had experienced changes in beliefs, questions about the meaning of life and increased anxiety around mortality.…”
Section: Existential Concerns Following End Of Treatmentmentioning
confidence: 99%